Seed treatment: an alternative and sustainable approach to cotton seed delinting - Zahra, Laviza Tuz; Qadir, Fariha; Khan, Mohammad Nasir; Kamal, Hira; Zahra, Nosheen; Ali, Arfan; Zafar, Muhammad Mubashar; Razzaq, Abdul; Jiang, Xuefei (Frontiers in Bioengineering and Biotechnology, 2024)
This review article delves into the vital aspects of cotton, emphasizing its global significance as a crucial agricultural commodity. The paper comprehensively explores the composition of cotton and surveys the diverse methods employed for the removal of cotton lint from seeds. Conventional delinting methods, including mechanical and chemical approaches, are scrutinized in terms of their advantages and drawbacks. However, the primary focus of this review is on highlighting the emerging significance of biological delinting methods. By harnessing the power of microbial enzymes and organisms, biological approaches offer a promising alternative for efficient lint removal. The authors discuss the environmental advantages associated with biological delinting, positioning it as a sustainable solution that mitigates the ecological impact of traditional methods. Furthermore, the article contextualizes these delinting methods within the framework of Sustainable Development Goals (SDGs) and underscores the importance of adopting eco-friendly practices in the cotton industry to align with SDG goals. By accentuating the potential of biological delinting in contributing to sustainable agriculture and responsible production, the review advocates for a paradigm shift towards more environmentally conscious approaches in the cotton sector. Overall, the article aims to provide a comprehensive perspective on cotton delinting methods, emphasizing the pivotal role of biological alternatives in fostering a sustainable and goaloriented future for the cotton industry.